PENGARUH LAMANYA PENYIMPANAN TERHADAP MUTU FISIK SEDIAAN SIRUP LORATADINE YANG SUDAH DIBUKA - indah trilestari (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
ABSTRACT Loratadine is a second-generation group of antihistamine drugs that block H1-receptors. In general, people use a solution of loratadine syrup at the time of allergy only, so the preparations are still left a lot and the public will tend to store the syrup. Drug preparations in the form of a solution or syrup are easily damaged. Research objectives : to determine the effect of the duration of storage of loratadine solution preparations and their significant value that has been opened for 15 days, 30 days and 45 days compared to 0 days as a control then conducted a physical quality test of loratadine solution preparations which includes organoleptic evaluation, pH determination test and level determination test. Research method : ecperimental using UV-Vis Spectrophotometry tool with a maximum wavelength of 247.0 nm. Before determining the value of the level performed lineritas value of y = 0.0308x + 0.0297. Research result : the results of organoleptic evaluation of loratadine solution preparations with a clear color, distinctive smell, bitter sweetness. Average pH result with 0 days of storage as control = 4.7 ; 15 days = 4.5 ; 30 days = 4.4 and 45 days = 4.5. And obtained the average yield percentage of the rate with a storage duration of 0 days as a control = 100.70%, 15 days = 101.19%, 30 days = 95.54%, and 45 days = 91.80%. Then the data of pH parameters and content of levels in the statistical test one way anova with a significant value of 0.000. Conclusion: in this study there are differences in physical quality in the preparation of loratadine syrup to variations in the length of storage after opening, namely in the parameters of pH and content of levels. Keywords: Loratadine, Syrup, Storage Duration, UV-Vis Spectrophotometry, pH, Dosage Content.